A platelet lipidomics signature in patients with COVID-19. (31st December 2023) - Goracci, Laura; Petito, Eleonora; Di Veroli, Alessandra; Falcinelli, Emanuela; Bencivenga, Caterina; Giglio, Elisa; Becattini, Cecilia; De Robertis, Edoardo; Vaudo, Gaetano; Gresele, Paolo
Abstract: Ischemic cardiovascular and venous thromboembolic events are a frequent cause of death in severe COVID-19 patients. Platelet activation plays a key role in these complications, however platelet lipidomics have not been studied yet. The aim of our pilot investigation was to perform a preliminary study of platelet lipidomics in COVID-19 patients compared to healthy subjects. Lipid extraction and identification of ultrapurified platelets from eight hospitalized COVID-19 patients and eight age- and sex-matched healthy controls showed a lipidomic pattern almost completely separating COVID-19 patients from healthy controls. In particular, a significant decrease of ether phospholipids and increased levels of ganglioside GM3 were observed in platelets from COVID-19 patients. In conclusion, our study shows for the first time that platelets from COVID-19 patients display a different lipidomics signature distinguishing them from healthy controls, and suggests that altered platelet lipid metabolism may play a role in viral spreading and in the thrombotic complications of COVID-19. Plain Language Summary: What is the context? Besides respiratory system involvement, venous thromboembolism is a severe complication of COVID-19, largely due to the strong derangement of hemostasis, with platelets playing a central role. Great attention has recently been devoted to lipid alterations in COVID-19, both because viruses by reprogramming cellular lipid metabolism remodel lipid membranes to fuel their replication, and because the COVID-19-associated cytokine storm may affect cell/plasma lipidomic signatures. Lipidomics studies in COVID-19 patients have been performed mainly in plasma and serum. To the best of our knowledge, platelet lipidomics have not been examined despite the central role played by platelets in COVID-19 complications. What is the aim of the study? The aim of our pilot study was to preliminarily explore whether platelet lipidomics is altered in COVID-19 patients compared to age- and sex-matched healthy subjects, analyzing lipidomic profile of ultrapurified platelets. What are the results of our study? Our study shows for the first time that platelets from COVID-19 patients display a different lipidomics signature distinguishing them from healthy controls. Ether phospholipids and, intriguingly, two phytoceramides were lower, while ganglioside GM3 was higher in COVID-19 samples compared to healthy controls. What is the impact? Despite the small number of COVID-19 patients enrolled, recognized as a limitation of our study, we show, for the first time, that platelets from COVID-19 patients present a different lipidomics signature and suggest that altered platelet lipid metabolism may play a significant role in viral spreading and in the thrombotic complications of COVID-19.